Preference of TCE (Traditional method of clinical Examination) Vs OSCE (Objective Structured clinical Examination) among the Final year B.Sc., Nursing students of selected College at Namakkal district –Comparative study. - Jothilakshmi , K. (International Journal of Rehabilitation and Special Education (IJRSE), 2021)
Clinical evaluation has always been an integral a part of nursing education. Examining the presence of professional behaviour, establishing an appropriate interaction with the patients, prioritizing the issues, possession of basic knowledge about clinical methods, correct performance of care procedures and execution of critical thinking are element of clinical evaluation. In India traditional method of practical examinations may be a while practice for evaluating students’ clinical performance. Recently most of the schools including medical university of Tamilnadu government introduced OSCE as a way of clinical examination for the nursing programme .This study designated to compare the preference of TCE (Traditional method of clinical Examination) Vs OSCE (Objective Structured clinical Examination) among the Final year B.Sc., Nursing students selected College at Namakkal district with the objectives to compare the preference of students regarding traditional method of Examination (TCE) with Objective Structured clinical Examination (OSCE) and to find out the association between the selected demographic value and preference regarding the method of examination. Methods: Research design adopted for this study was Quantitative research approach with non experimental Descriptive Comparative design. 60 Final year B.Sc. nursing students of Dhanvantri College of nursing at Namakkal District were selected as sample by adopting Non probability convenient sampling technique. Results: Calculated mean and standard deviation value of students preference regarding TCE is 18.6 ,4.06, where in case of OSCE is 32.3, 5.5 with mean difference 13.7. Discussion: mean value revealed that the majority of respondents were identified to have positive perceptions on OSCE